Assessing farmers’ awareness towards climate change in the middle part of Bangladesh - Al Mahamud, Tanbir; Hasan, Shaikh Shamim; Ghosh, Mithun Kumar; Chakma, Prabin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Climate change is known to have a severe influence on agriculture, posing a serious danger to the food security and livelihoods of rural people, hence, public understanding about climate change must be encouraged in order to facilitate mitigation and adaptation strategies. Therefore, the main purpose of this study was to determine farmers’ awareness towards climate change. The study was conducted in three villages of Sadar upazila of Gazipur district (middle part) of Bangladesh. A total number of 110 farmers were selected as sample following proportionate random sampling technique. The findings of the study revealed that about 65% farmers were in between 30 to 50 years with secondary to SSC level of education (72%) and had ‘5 to 6’ members of family size. For acquiring extension information, the farmers mainly communicated with SAAOs and seed dealers. Out of all the respondent farmers, 83% had their own land for cultivating different types of crops, and 86% of them received 1 to 6 no. of agriculture related training, although 98% of them did not involve themselves to receive any website help for conducting better agricultural activities. Moreover, 83% farmers had moderately to highly favorable awareness to climate change (both causes and effects). In addition, out of the selected attributes, three attributes, namely, age, agricultural training received, and knowledge on climate change had significant contribution on the awareness to climate change. The study provided new empirical evidence on the awareness level of farmers to climate change on agriculture, in general. The findings of the study can be utilized by the policy makers of the country to formulate proper mitigation and adaptation options to future climate change and its’ impact on agriculture.